Enhancing Environmental Literacy in Palestine: Reflecting on Secondary School Students’ Knowledge and Attitudes - Abdullah, Murad Awadallah (Journal of Educational and Psychological Sciences, 2021)
In the past, since the first Earth Day, organizations have endorsed the development of well informed and environmentally literate citizen as the answer to our threatened environment. According to many Environmental Education (EE) experts, knowledge and attitudes are important components of environmental literacy (EL), especially if the goal of environmental education is to change behavior. In our study, a questionnaire with two parts was randomly distributed to 49 selected schools which included 942 10th grade students in Palestine, with a 100% response rate. Results showed that participants had favorable attitudes toward the environment which ranged from 57.5 to 74.8 out of 100 points. The environmental knowledge scores are topicality, fragmentary or incorrect, which range from 45.72 to 67.36. Significant differences were found in the level of EL scores by gender. Educational implications and recommendations are discussed.